SURVIVING STRATEGY OF TOURISM SECTOR WORKERS IN BANDUNG DURING THE COVID-19 PANDEMIC - Silvia Septyani Koswara; Ahmad Hudaiby Galih Kusumah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The Covid-19 pandemic has had an impact on social and economic life, especially in Indonesia. In the city of Bandung itself, this impact is felt for workers in the tourism sector such as travel business owners, tour leaders, tour guides and tourism bus drivers. The writing of this research was carried out with the aim of knowing the negative impacts felt by tourism sector workers in the city of Bandung during the Covid-19 pandemic. In this study, the authors used a direct interview method using a semi-structured interview guide instrument, with the direction of the interview aimed at: 1) Knowing the impact of the Covid-19 Pandemic felt by tourism workers. 2) Knowing the survival strategies carried out by tourism workers during the Covid-19 Pandemic. From the two subtitles, it can be seen that the direct impact of the Covid-19 pandemic on tourism business actors in the city of Bandung is seen from the income aspect. Most tourism workers in Bandung City have lost their livelihoods during the Covid-19 pandemic. So that requires tourism business actors to change professions in order to survive, such as: a) Selling used cars. b) Selling designs online. c) Selling catering. d) Changing the vehicle business unit from tourism buses to inter-island buses. e) Become a private driver or online. f) Selling used clothes online. g) Selling juice and hydroponic vegetable cultivation. h) Opening employment opportunities for other affected tourism business actors in the form of local courier applications in the city of Bandung. i) Selling frozen food.